Pengaruh Model Pembelajaran Round Club Terhadap Keterampilan Berbicara Siswa Kelas IV UPT SPF SD Inpres Mandai Kota Makassar - Puang Maharani, Putri Brasil; Adam, Andi; Rahmatiah, Rahmatiah (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
AbstractPutri Brasil Puang Maharani, 2025. The Effect of Round Club Learning Model on Speaking Skills of Fourth Grade Students of UPT SPF SD Inpres Mandai, Makassar City. Thesis. Department of Elementary School Teacher Education (PGSD), Faculty of Teacher Training and Education, Muhammadiyah University of Makassar supervised by Andi Adam and Rahmatiah.The main problem of this study is whether there is an effect of implementing the Round Club learning model on the speaking skills of students of UPT SPF SD Inpres Mandai, Makassar City. This study aims to describe the effect of the Round Club learning model on the speaking skills of fourth grade students of UPT SPF SD Inpres Mandai, Makassar City.This type of research is a pre-experimental research in the form of Pretest Posttest Design, namely an experiment that in its implementation only involves one class as an experimental class without a comparison class (control class) which aims to determine the Effect of the Round Club Learning Model on the Speaking Skills of Fourth Grade Students of UPT SPF SD Inpres Mandai, Makassar City. The subjects of this study were 23 fourth grade students of UPT SPF SD Inpres Mandai, Makassar City.The results of the study showed that the learning outcomes of fourth grade students before the implementation of the Round Club learning model that was completed individually from 23 students were only 8 students or 34.78% who met the Minimum Completion Criteria (KKM) or were in the low category. Classically it has not been met because the average pretest score is 62.6%. While when implementing the Round Club learning model that was completed individually from 23 students, there were 21 students or 91.30% who had met the KKM and classically it had been met, namely the average posttest score obtained was 85.2% which was categorized as high. This proves that there is an Influence of the Round Club Learning Model on Speaking Skills in Fourth Grade Students of UPT SPF SD Inpres Mandai, Makassar City.Keywords: Pre-Experiment, Round Club Model and Speaking Skills